SPEED CONTROL OF THREE-PHASE INDUCTION AC MOTOR FOR ROLLER RIG USING PID CONTROLLER TUNING METHOD - Abdul Rahman, Hafiz
The implementation of a roller rig as an initial testing device for trains at a 100% scale in Indonesia is a primary necessity. Roller rigs are typically powered by three-phase induction AC motors with a precise speed control system. Such a control system is already available in the Dynamics Laboratory of ITB. However, the system still requires modifications and further testing to find the most optimal configuration with optimal performance. To meet this need, this final project will involve the modification and retesting of the device. This final project consists of two research stages: modification of the control system and performance testing of the control system. Modifications include aspects such as improving the loading system, enhancing the measurement system, adding a Human Machine Interface (HMI), and more. After the system is modified, performance testing of the control system is carried out using two speed profiles and two speed targets that comply with the requirements of a roller rig. These profiles and targets are achieved by tuning the system using five methods: Ziegler-Nichols, Cohen-Coon, Chien-Hrones-Reswick, Lambda, and Wang-Juang-Chan. The research results indicate improvements in the control system concerning loading and measurement, axial rotor position consistency, ease of control system operation, and more. For system tuning, it is known that the best method is Cohen-Coon with PID control strategy because it can resist disturbances, produce a settling time of 43.091 seconds and a time delay of 1,821 seconds.